Impact of financial innovation and financial inclusion on sustainable rural development - S, Dr. Umakanth; Kumar S, Dr. Hemanth; Iyer K N, Dr. Anantha Subramanya (The journal of contemporary issues in business and government, 2023)
Rural banking has made some great achievements, but problems like the uneven distribution of credit across developed and less developed regions, the low amount of institutional credit held by low-income groups and their reliance on non-institutional sources, nevertheless loom larger than ever. Due to this, ensuring that institutional funding of rural areas enhances financial inclusion is currently the most crucial issue. Financial innovation is essential for long-term rural development. This investigation seeks to identify that role. The information was acquired from those in rural Bangalore who had benefited from financial inclusion programs. The study’s nature is descriptive. The questionnaire was prepared after a thorough review of the pertinent literature and consultation with industry professionals, and it was then put through extensive testing to confirm its validity and reliability. Using the convenience sampling method, 121 participants were selected from Hoskote Taluk, Devanahalli Taluk, Dodballapur Taluk, and Nelamangala Taluk in the Bangalore rural district. Simple frequency and percentage analysis, descriptive statistics, and a scale’s reliability and validity were all evaluated using the SPSS program. To analyze mediation, the Andrew Hayes process model 4 was used. The importance of financial inclusion for sustainable development is highlighted by the fact that, despite the lack of a direct link between the two concepts, the cumulative impact of the relationship is considerable. It is crucial to achieve the highest level of sustainable development and to increase financial inclusion by designing financially creative solutions that meet the demands of the rural poor. This research adds significantly to the area, despite the fact that financial inclusion has long been recognized as an essential component of socioeconomic empowerment.